Traditional Clothes of the Women of the Takchi Tribe of the Surkhan Oasis (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the ethnocultural processes of the Tokshi people living in the Surkhan oasis are covered by a scientific analysis of some works of the philologists Bilqiz Karimsheva and O.A. Sukhareva. The traditional clothes of the women of the Takchi people and the dyeing of the fabric, the methods of fabric preparation, the types of fabric and the history of sewing women's clothing are shown.